Civil law contracts and the profession of a teacher - Szadkowska, Ewelina (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The subject matter of the article is the admissibility of concluding civil law contracts to employ teachers, considering the specific character of this occupational group. A change in the regulations regarding the ban on employing teachers under such contracts encourages reflection and some comments on its legitimacy. The author describes the benefits gained from this modification by teachers employed at non-public schools, as well as the losses potentially suffered by employers. The change in the law came into force on 1 September 2018 and is viewed differently by headteachers and regular teachers. In the final part of the article, the author presents her own opinion on this issue.